USAGE OF A RAPID DIAGNOSTIC TEST FOR MALARIA IN CHILDREN - Nkenfou, Céline Nguefeu; Hell, Vestale Ngo; Georges, Nguefack-Tsague; Ngoufack, Marie Nicole; Nkenfou, Carine Nguefeu; Kamgaing, Nelly; Ndjolo, Alexis (African Journal of Infectious Diseases (AJID), 2018)
Background: Malaria is still the primary cause of pediatric deaths. The efficient management of pediatric malariarequires its rapid and accurate diagnosis. To fulfill this requirement, rapid diagnostic tests have been developed, buttheir evaluation before commercialization is never exhaustive. The aim of this study was to evaluate the performance ofa rapid diagnostic test (SD Bioline Malaria Antigen P.f/Pan) to diagnose malaria in children.Materials and Methods: Testing was conducted on children aged between 6 months and 15 years who were examinedat the CME-FCB as a result of fever. Enrollment took place from April to October 2014. All children presenting withfever were sampled (3ml of blood). These blood samples were tested for malaria using microscopy on a thick bloodsmear and by a rapid diagnostic test (RDT) SD Bioline Malariae Antigen P.f/Pan.Results: A total of 249 children were enrolled in this study. Malaria presence as determined by microscopy and byRDT was 30.9% and 58.2% respectively. The sensitivity, specificity, positive and negative predictive values comparedto microscopy were: 75; 48.8; 39, and 81.6%. With these performances, the malaria SD Bioline rapid test presentslower values compared to WHO recommendations for rapid tests (sensitivity > 95%) in children.Conclusion: SD Bioline Malaria Antigen P.f/Pan test should only be used in peripheral health structures that lackresources, and should be aided by clinical diagnosis.